Artemether-loaded nanostructured lipid carriers: preparation, characterization, and evaluation of in vitro effect on Leishmania major - Vahid Rahnama; Mohammad Hossein Motazedian; Soliman Mohammadi-Samani; Qasem Asgari; Parisa Ghasemiyeh; Meisam Khazaei (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Cutaneous leishmaniasis is a global health problem. The discovery of new and highly efficient anti-leishmanial treatments with lower toxicity is globally needed. The current study was carried out to evaluate the anti-leishmanial effects of artemether (ART) and ART-loaded nanostructured lipid carriers (ART-NLCs) against promastigotes and amastigotes of Leishmania major. Experimental approach: Solvent diffusion evaporation technique was applied to prepare ART-NLCs. These nanoparticles were characterized using a particle size analyzer (PSA), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The antiparasitic activity on amastigote was assessed in J774 cell culture. The drug cytotoxicity on promastigote and macrophage was assessed using the MTT technique after 24 and 48 h and compared with NLCs, ART, and amphotericin B, as the control agents. The selectivity index was calculated for the agents. Findings/Results: The DLS and PSA techniques confirmed that ART-NLCs were homogenous in size with an average diameter of 101 ± 2.0 nm and span index of 0.9. The ART-NLCs significantly heighten the anti-leishmanial activity of ART (P < 0.001). The IC50 values of ART and ART-NLCs on promastigotes after 24 and 48 h were 76.08, 36.71 and 35.14, 14.81 μg/mL, respectively while they were calculated 53.97, 25.43 and 20.13, 11.92 for amastigotes. Also, ART-NLCs had the lowest cytotoxicity against macrophages. Furthermore, among the agents tested, ART-NLCs had the highest selectivity index. Conclusion and implications: ART-NLCs had lower cytotoxic effects than ART and amphotericin B, also its selectivity index was significantly higher. Based on the findings of the study, this formulation could be a promising candidate for further research into leishmaniasis treatment.